2014
DOI: 10.1590/s1413-24782014000900009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação comparativa dos sintomas da síndrome de burnout em professores de escolas públicas e privadas

Abstract: Atualmente, observa-se em parte dos docentes em exercício um sentimento de desmotivação em relação à sua profissão. Frequente entre os educadores, a síndrome de burnout caracteriza-se pela perda do sentimento de realização no trabalho, com produtividade diminuída. Nesse contexto, objetivou-se avaliar a presença dos sintomas dessa síndrome entre profissionais do ensino público e privado no município de Viçosa/MG, de modo que se identificasse qual grupo estaria mais predisposto a desenvolvê-la. Os dados obtidos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 5 publications
3
6
0
10
Order By: Relevance
“…Sociodemographic This multivariate factor regression analysis was based on n = 1607 and adjustment for all variables factors, such as the type of school, income satisfactory and BMI, emerged as statistically significant predictors with burnout (Table 2). We found that teachers who worked in public schools showed a higher rate of burnout than teachers who worked in private schools, which is consistent with previous studies [15,35]. There are higher job requirements, stricter teaching management and assessment in the public kindergartens than in the private kindergartens and parents have higher expectations for public kindergarten teachers, which maybe inevitably lead to more mental pressure on public kindergarten teachers.…”
Section: Discussionsupporting
confidence: 90%
“…Sociodemographic This multivariate factor regression analysis was based on n = 1607 and adjustment for all variables factors, such as the type of school, income satisfactory and BMI, emerged as statistically significant predictors with burnout (Table 2). We found that teachers who worked in public schools showed a higher rate of burnout than teachers who worked in private schools, which is consistent with previous studies [15,35]. There are higher job requirements, stricter teaching management and assessment in the public kindergartens than in the private kindergartens and parents have higher expectations for public kindergarten teachers, which maybe inevitably lead to more mental pressure on public kindergarten teachers.…”
Section: Discussionsupporting
confidence: 90%
“…Sociodemographic factors, such as the type of school, income satisfactory and BMI, emerged as statistically significant predictors with burnout ( Table 2). We found that teachers who worked in public schools showed a higher rate of burnout than teachers who worked in private schools, which is consistent with previous studies [15,35]. There are higher job requirements, stricter teaching management and assessment in the public kindergartens than in the private kindergartens and parents have higher expectations for public kindergarten teachers, which maybe inevitably lead to more mental pressure on public kindergarten teachers.…”
Section: Discussionsupporting
confidence: 90%
“…Em escolas públicas, são ressaltados problemas relacionados a baixos salários, formação continuada deficitária para corresponder às atuais demandas educacionais, violência dos alunos (Levy, Nunes Sobrinho, & Souza, 2009), falta de apoio dos pais e da direção da escola, sobrecarga de trabalho e cobrança social (Diehl & Carlotto, 2014). No ensino privado, por sua vez, evidenciam-se sentimentos de insegurança diante de uma possível demissão (Dalagasperina & Monteiro, 2014) e o excesso de cobranças (Esteves-Ferreira Santos, & Rigolon, 2014)…”
Section: Resultsunclassified